MAPPING OF MANGROVE DISTRIBUTION AND SPATIAL ANALYSIS OF LAND SUITABILITY FOR POND AQUACULTURE IN COASTAL AREA OF GENDING SUB DISTRICT, PROBOLINGGO - Abu Bakar Sambah; N Harahap; M Mahmudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2014)
The research on mapping of mangrove distribution and spatial analysis of land suitability for pond aquaculture in coastal area of Gending sub District, Probolinggo are to map the distribution of existing mangrove forests along the coastal area of Gending and to determine the land suitability for aquaculture activities. This research used Landsat satellite imagery as an initial imaging data of the study area. Band manypulation using visual band 3-2-1, 4-3-2 and infrared bands 4-5-3. The use of this band based on their sensitivity in capturing the value of a high reflectance of vegetation. Rupa Bumi Indonesia Map scale 1: 25,000 from Bakorsurtanal used as a correction of satellite imagery. Furthermore, the survey field mapping with a model of participatory mapping done to calibrate the field data and sampling of water quality in the study area.Based on the analysis of satellite image and survey found that mangroves are spread almost evenly along the coastal area of Gending with a high density (visually) and identified along the coordinates of 762720 mT, 9144134 mU and 795851 mT, 9144081 mU. While the aquaculture area identified spread along the coastal with the coordinates 751394 mT, 9138874 mU to 776632 mT, 9147895 mU. Through the spatial analysis of land suitability described that most of the pond in the western part of coastal area is very suitable for aquaculture activities. Keywords: Mapping, mangroves, land suitability